Re‐Purposing Business Schools: Potential, Progress, and Precarity - Kitchener, Martin (Journal of Management Studies, 2024)
AbstractWith recent management studies of organizational purpose concentrating on the reactions of corporate elites to external change stimuli, little attention has been given to the emergent phenomenon of internally‐driven business school re‐purposing. Breaking with a tradition of incremental change in the field, re‐purposing denotes a transformational process that arises from business school leaders' attempts to focus their organizations on the pursuit of their purpose to enhance the public good, from management scholarship and the way that business schools operate. This paper frames business school re‐purposing as the endogenous enactment of a purpose logic, and it draws from early cases in the UK and France to present an analysis of the leadership activity involved. The potential for further business school re‐purposing is assessed critically with reference to general challenges of infusing purpose into organizations, and the specific threats posed by a field that is dominated by a countervailing logic of purpose, a conservative approach to management, and increasing financial pressures.